2*m+11=4*m*11

Simple and best practice solution for 2*m+11=4*m*11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2*m+11=4*m*11 equation:


Simplifying
2m + 11 = 4m * 11

Reorder the terms:
11 + 2m = 4m * 11

Reorder the terms for easier multiplication:
11 + 2m = 4 * 11m

Multiply 4 * 11
11 + 2m = 44m

Solving
11 + 2m = 44m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-44m' to each side of the equation.
11 + 2m + -44m = 44m + -44m

Combine like terms: 2m + -44m = -42m
11 + -42m = 44m + -44m

Combine like terms: 44m + -44m = 0
11 + -42m = 0

Add '-11' to each side of the equation.
11 + -11 + -42m = 0 + -11

Combine like terms: 11 + -11 = 0
0 + -42m = 0 + -11
-42m = 0 + -11

Combine like terms: 0 + -11 = -11
-42m = -11

Divide each side by '-42'.
m = 0.2619047619

Simplifying
m = 0.2619047619

See similar equations:

| 85x+1.10x=280 | | 6i^28=i | | 15x+5(.75x)=90 | | 6i^28=x | | 85x+280+1.10x=0 | | 8x^3+6x^2+x=0 | | (1b-8)(5b-2)= | | 15x+5y=90 | | (B-8)(5b-2)= | | 7(9x)+4= | | (x^2-25)= | | 3x-7=48-12x | | (6a-3)(4a-1)= | | x^2-12x+36=18 | | w-2=0 | | x^2+5x-3=3 | | 15a+8b-4a-b= | | 3-2t+1=12 | | 5t^2-7t-1=0 | | 1+5t+5=16 | | 5t^2-7+1=0 | | 15x+7=-19+2x | | 2e-12=7e+15 | | 3x+6y=20 | | 0.5(0.5x)(x)=196 | | 1-5t+5=16 | | 4z^4+2z^3-4z=0 | | 2x+2=4x-4 | | 16t^2+10t=174 | | 5a+a=246 | | p-0.60p=644 | | 4d^2(-2d^3+5d^2-6d+2)= |

Equations solver categories